Do better : spiritual activism for fighting and healing from white supremacy - Ricketts, Rachel, 1984- (Atria Books, 2021)
"Thought leader, racial justice educator, and sought-after spiritual activist Rachel Ricketts offers mindful and practical steps for all humans to dismantle white supremacy on a personal and collective level"--